2015
DOI: 10.1016/j.joca.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritic changes in vervet monkey knees correlate with meniscus degradation and increased matrix metalloproteinase and cytokine secretion

Abstract: Objective Meniscus injury increases osteoarthritis risk but its pathobiology in osteoarthritis is unclear. We hypothesized that older adult vervet monkeys would exhibit knee osteoarthritic changes and the degenerative menisci from these animals would secrete matrix metalloproteinases (MMPs) and pro-inflammatory cytokines that contribute to the development of osteoarthritis. Design In a cross sectional analysis of healthy young adult (9-12 years) and old (19-26 years) adult female vervet monkeys, knees were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The expression of MMP1 and MMP3 has also been shown to be elevated in the synovial fluid of patients with OA 24 . A recent animal study demonstrated elevated expression of MMP1 and MMP3 from the menisci of knees with OA compared to menisci from knee without OA 26 . However, MMP3 expression was lower in the meniscus of human patients with OA compared to controls 20 , which is congruent with our findings that traumatic meniscus tears have elevated MMP-3 compared to degenerative meniscus tears.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of MMP1 and MMP3 has also been shown to be elevated in the synovial fluid of patients with OA 24 . A recent animal study demonstrated elevated expression of MMP1 and MMP3 from the menisci of knees with OA compared to menisci from knee without OA 26 . However, MMP3 expression was lower in the meniscus of human patients with OA compared to controls 20 , which is congruent with our findings that traumatic meniscus tears have elevated MMP-3 compared to degenerative meniscus tears.…”
Section: Discussionmentioning
confidence: 97%
“… 20 Although not evaluated in human meniscus with aging, nonhuman primate meniscus-explant cultures exhibited increased MMP1 and MMP3 in older degenerated versus younger healthy menisci. 21 With menopause, FC AC, TP AC, and MM exhibited no changes in MMPs and TIMPs, but LM exhibited decreases in TIMPs. In AC, collagen was decreased (TP AC), but proteoglycans were increased (FC AC and TP AC).…”
Section: Discussionmentioning
confidence: 98%
“…One of the most remarkable findings of the present study was the decrease in concentration of the cytokine GM-CSF in knee joint synovial fluid of all subjects following the run. This result is particularly interesting because synovial fluid GM-CSF is known to be significantly elevated in cases of knee OA and rheumatoid arthritis (RA) (Cameron et al 1997;Arend and Dayer 1990), as well as in cases of knee injury that precede knee OA (Stone et al 2015). Further, it is believed that neutralization of GM-CSF might effectively control OA pain and progression (Cook et al 2012).…”
Section: Discussionmentioning
confidence: 99%